Pengembangan Putusan Hakim terhadap Dispensasi Pernikahan di Pengadilan Agama Belopa (Tinjauan Maqāṣid Syarī’ah): Development of Judicial Decisions on Marriage Dispensation at the Belopa Religious Court (Maqashid Sharia Perspective) - Darmawati, Darmawati; Wildana Arsyad (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This study aims to analyze the factors influencing judicial decisions, evaluate the alignment of these decisions with the principles of Maqashid Sharia, and formulate recommendations for more comprehensive decision-making. This research employs a qualitative method with a normative-juridical and empirical approach. Data was collected through a study of court decisions, in-depth interviews with judges at the Belopa Religious Court, and observation of court proceedings. Data analysis was conducted using Maqashid Sharia theory, specifically its five main principles: protection of religion, life, intellect, lineage, and property. The study results reveal variation in judges' considerations for granting marriage dispensations. Factors such as premarital pregnancy, concerns about possible adultery, and social pressures often underlie the granting of dispensations. The Maqashid Sharia analysis indicates that some decisions tend to prioritize the protection of lineage and religion, but lack consideration for the protection of intellect and life, particularly regarding the mental and physical readiness of young couples.